Complementary and Alternative Treatment Use in Breast Cancer Patients in the Eastern Black Sea Region—A Cross-Sectional Study - Dişli, Şafak; Fidan, Evren; Özdöver, Ali; Kazaz, Nazlı; Özdemir, Feyyaz (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Complementary and alternative therapies (CAMs) are being increasingly and frequently used in the treatment of cancer patients in the last two decades.Objectives It was aimed to examine the frequency of the use of CAMs in patients with breast cancer who applied to the outpatient clinic.Materials and Methods Patients who were admitted to our clinic between January 2020 and 2021 and diagnosed with breast cancer for at least 3 months were included in the study. A questionnaire consisting of 37 questions was asked to the patients by the interviewer. Sociodemographic characteristics and CAM methods of the patients were questioned in the questionnaire.Results This is a cross-sectional study that includes 338 patients. After the questionnaire was completed, the answers were evaluated, and it was detected that 147 (43.4%) patients were using CAM. Herbal treatment methods were preferred most frequently. The most frequently used herbs were turmeric, nettle, ginger, and linden. The second method used was treatments based on religious belief. The use of CAM increased as the income level of the patients increased and the duration of diagnosis increased.Conclusion It was determined that our patients frequently used CAM methods and mostly preferred herbal methods. Since the use of CAMs during or after treatment may create undesirable results in the treatment of patients, it is necessary to be careful about this issue and inform as well as question the patients about the same.
Keywords: breast cancer; complementary and alternative therapies; herbal